2004
DOI: 10.1021/ja036958m
|View full text |Cite
|
Sign up to set email alerts
|

New Caged Coumarin Fluorophores with Extraordinary Uncaging Cross Sections Suitable for Biological Imaging Applications

Abstract: Photocaged fluorescent molecules are important research tools for tracking molecular dynamics with high spatiotemporal resolution in biological systems. We have designed and synthesized a new class of caged coumarin fluorophores. These coumarin cages displayed more than 200-fold fluorescence enhancement after UV photolysis. Remarkably, the uncaging cross section of a 1-(2-nitrophenyl)ethyl (NPE)-caged coumarin is 6600 at wavelength of 365 nm, about 2 orders of magnitude higher than previously described caged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(184 citation statements)
references
References 25 publications
4
173
0
7
Order By: Relevance
“…30 This moiety was chosen due to its capability of undergoing two-photon photolysis 37 (at 740nm the two-photon cross section δ u Φ u ≈ 0.01 to 0.03 GM 38 ) and its previous use in biological systems. 39 Upon two-photon excitation, PEGdiPDA cleaves between the NBE and acrylate functionalities, releasing modified PEG and polyacrylate chains with pendant PEG. Previous studies have shown that the degradation products of this hydrogel formulation are cytocompatible.…”
Section: Resultsmentioning
confidence: 99%
“…30 This moiety was chosen due to its capability of undergoing two-photon photolysis 37 (at 740nm the two-photon cross section δ u Φ u ≈ 0.01 to 0.03 GM 38 ) and its previous use in biological systems. 39 Upon two-photon excitation, PEGdiPDA cleaves between the NBE and acrylate functionalities, releasing modified PEG and polyacrylate chains with pendant PEG. Previous studies have shown that the degradation products of this hydrogel formulation are cytocompatible.…”
Section: Resultsmentioning
confidence: 99%
“…Embryonic neurons were isolated from nsy-5p::mCherry transgenic animals, in which neurons of the NSY-5 network were labeled with mCherry (Shaner et al, 2004;Shaner et al, 2005). Cultured neurons were loaded with the cell-permeable caged fluorophore NPE-HCCC2/AM (Zhao et al, 2004;Dakin et al, 2005). After entering the cell, the acetoxymethyl (AM) esters are hydrolyzed and the caged dye (NPE-HCCC2) becomes trapped inside the cell.…”
Section: Nsy-5 Gap Junctions Mediate Small Molecule Transfer Between mentioning
confidence: 99%
“…Several different o-NB groups have been reported [14][15][16] , and small modifications to the structure of the o-NB linker have a significant impact on the photolysis rate. 14 The benzylic position (photodegradation site) of o-NB groups can be primary or secondary (Chart 1a, R 1 = −H or R 1 = −CH 3 ).…”
Section: Introductionmentioning
confidence: 99%